Empowering MSMEs: The Role of Mosques in Community Economic Development - Indin Rarasati; Unggul Priyadi (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
Mosques hold significant potential in community development, particularly through the management of zakat, infaq, and sadaqah to empower Micro, Small, and Medium Enterprises (henceforth MSMEs). This study explores the role of Jogokariyan Mosque, a unique and famous mosque located Â in Yogyakarta Indonesia, as a zakat administrator in supporting MSMEs empowerment. Utilizing primary data from in-depth interviews and content analysis, this case study highlights the mosque's initiatives, including kindness loans, business training, and market creation. The key informant, Mr. Jardi, an administrator of Jogokariyan Mosque, was selected through purposive sampling. The research adopts a triangulation method, involving pre-field analysis, data interpretation and classification, data reduction, and conclusion verification. The findings reveal that Jogokariyan Mosque, through its institution Lembaga Amil Zakat (LAZ), effectively collects, manages, and distributes zakat funds, providing essential support to MSMEs and enhancing community welfare. This research underscores the crucial role of mosques in economic development and community empowerment. Last but not least, this research offers valuable insights for policymakers, religious leaders, and community organizers on the potential of mosques to serve as central hubs for economic empowerment through zakat management.